2000
DOI: 10.1161/01.cir.101.8.886
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Patterns in Sympathetic Neural Discharge and Cardiovascular Variables During Orthostatic Stimulus

Abstract: During the sympathetic activation induced by tilt, a similar oscillatory pattern based on an increased LF rhythmicity characterized the spontaneous variability of neural sympathetic discharge, R-R interval, and arterial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
273
4
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(319 citation statements)
references
References 32 publications
29
273
4
6
Order By: Relevance
“…Therefore, future trials designed to test the ability of respiratory-gated symbolic analysis should account for the previous observation to compute the sample size. The smallness of the sample size of this study was emphasized also by the inability to detect the decrease of the HP variance and the increase of the SAP variance during TILT [31][32][33]35]. The non-significant trends observed in this study during TILT might turn into significant differences if the sample size was augmented.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, future trials designed to test the ability of respiratory-gated symbolic analysis should account for the previous observation to compute the sample size. The smallness of the sample size of this study was emphasized also by the inability to detect the decrease of the HP variance and the increase of the SAP variance during TILT [31][32][33]35]. The non-significant trends observed in this study during TILT might turn into significant differences if the sample size was augmented.…”
Section: Discussionmentioning
confidence: 69%
“…This finding suggested that coupling between fast features of MSNA and SAP series, quantified by 2UV-2UV%, plays a significant role in the MSNA-SAP coordination. Remarkably, orthostatic challenge significantly reduced 2UV-2UV%, thus suggesting that sympathetic overactivity and/or the increase of sympathetic modulation was able to reduce this type of coordinated MSNA-SAP behaviour probably by augmenting the importance of slower rhythms [32].…”
Section: Discussionmentioning
confidence: 91%
“…Low-frequency blood pressure oscillations, the so-called Mayer waves, are mediated by the sympathetic nervous system. 24,25 Similarly, selective norepinephrine transporter blockade with reboxetine attenuates low-frequency systolic blood pressure oscillations. 12 Moreover, we observed a marked reduction in venous plasma norepinephrine concentration with sibutramine.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have implied that the LF component of HRV as well as the LF/HF ratio might reflect the parasympathetic cardiac modulation or the baroreflex 13,28 , the LF component has usually been associated with sympathetic activity 29,30 . In the present study, there was an increase in the LF/HF component of HRV in the infarcted animals.…”
Section: (5) 2016 -343mentioning
confidence: 99%